2020
DOI: 10.1021/acs.analchem.0c00673
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Multiphoton Imaging of the Lipid Bilayer by Dye-Based Sum-Frequency Generation and Coherent Anti-Stokes Raman Scattering

Abstract: Coherent anti-Stokes Raman scattering (CARS) imaging is widely used for imaging molecular vibrations inside cells and tissues. Lipid bilayers are potential analytes for CARS imaging due to their abundant CH 2 vibrational bonds. However, identifying the plasma membrane is challenging since it possesses a thin structure and is closely apposed to lipid structures inside the cells. Since the plasma membrane provides the most prominent asymmetric location within cells, orientation sensitive sum-frequency generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Taking advantage of the non-fluorescent SFG-active Ap3 dye, we were able to image the lipid structures of living cells using CARS in combination with specific plasma membrane imaging by SFG (Fig. 7) (Mizuguchi et al 2020). Therefore,…”
Section: Multimodal Multiphoton Imagingmentioning
confidence: 99%
“…Taking advantage of the non-fluorescent SFG-active Ap3 dye, we were able to image the lipid structures of living cells using CARS in combination with specific plasma membrane imaging by SFG (Fig. 7) (Mizuguchi et al 2020). Therefore,…”
Section: Multimodal Multiphoton Imagingmentioning
confidence: 99%
“…Nuriya et al synthesized a SHG-specific dye (AP3) that exhibited desirable SHG intensity on the cell membrane with virtually no TPF signal . Then, AP3 was used in multimodal multiphoton imaging with coupling of sum-frequency generation and coherent anti-Stokes Raman scattering to detect the characteristics of lipid bilayers in giant vesicles and living cells. , SHG is a second-order nonlinear coherent scattering process in which two photons with optical frequency ω are converted to a single photon with an optical frequency of 2ω after interacting with nonlinear optical (NLO) materials. ,, Therefore, the SHG process enables a redshift of the laser wavelength into the infrared window, allowing high-resolution deep-tissue imaging. …”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, MG (malachite green) and D289 (( E )-4-(4-(diethylamino)­styryl)-1-methylpyridin-1-ium) were commonly used as SHG-active molecules. MG has a relatively high SHG efficiency and low TPF emission, so it has been used in studying energetics during its adsorption and interactions with interfaces, including gas–solid, gas–liquid, solid–liquid, and water lipid interfaces. , It is also known that MG has a higher SHG efficiency in acidic bulk solutions (pH = 4); D289 is suitable for use in neutral environments, which better resembles the biological environment. ,,, It was observed that D289 emitted a strong TPF signal, especially when it was dispersed in lipid membranes, , although this TPF differs in wavelength from the SHG emission and can be separated in spectral measurements. It is known that dyes emitting strong fluorescence may generate unwanted fluorescence backgrounds and cross-modal interference when used in multiple imaging systems, ,, which could decrease the resolution of images in a large scale. For this reason, a SHG-specific dye with good nonlinear efficiency and suppressed TPF emission is highly desired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the SRS-CARS microscope system and data analysis are described in SI-2. 11,41,42) SRS and CARS signals were acquired by adjusting the wavenumber difference between the pump and Stokes beams to ∼2093 cm −1 , which approximately corresponds to the aforementioned alkyne vibration energy ( i.e. on-resonance).…”
mentioning
confidence: 99%